Gestión emocional y violencia intrafamiliar - Cacoango Cando, Karen Gisell (2024)
This research study aimed to analyze emotional management and domestic violence in sixth- grade students of General Basic Education at Unidad Educativa “Cicalpa.” A mixed approach was adopted to collect accurate and detailed information, thus allowing one to examine the reality surrounding these issues. The study´s design was non- experimental due to its exploratory nature since it was a field and bibliographic research. The study sample included 15 sixth- grade students, the area teacher, and the educational psychologist of the institution. It was necessary to use survey and interview techniques by employing a questionnaire and a guide of structured questions as instruments. The most out outstanding results revealed that most students have difficulties identifying and expressing their emotions, demonstrating poor emotional management in various daily situations, individually and in their interactions. Regarding domestic violence, it was possible to identify a low rate of this problem. However, the researcher identified a severe lack of awareness and emotional expressiveness within the homes; therefore, it is necessary to consider this factor. The study concludes that there are no stable family relationships based on emotional dialogue, which puts the students' physical, psychological, social, and educational well-being at risk and the integral development of their personality.